Union Yes bus, 1990 (London, 1990)
1990 1980-95 "Union Yes bus, 1990" [BW0085], 1990, Trades Union Congress As part of the Union Yes campaign to promote trade union organisation and recruitment, a Women's Help Bus toured Greater Manchester and the London Docklands area offering information and advice on equal pay and other issues important for women workers. Women trade union officers (l-r): Donna Covey, Gloria Mills, Pam Thomas, Rita Donaghy, Maureen Twomey, Helen McGrath, Bernadette Hillon.